Workers' experience with work-related musculoskeletal disorder and worker's perception of organisational policies and practices. Issue 1 (6th February 2017) - Oranye, Nelson Ositadimma; Wallis, Bernadine; Ahmad, Nora; Aguilar, Zaklina
Abstract : Purpose: Different organisations have developed policies and programmes to prevent workplace injuries and facilitate return to work. Few multiple workplace studies have examined workers' perceptions of these policies and programmes. The purpose of this paper is to compare workers' perception and experience of workplace policies and practices on injury prevention, people-oriented work culture, and return to work. Design/methodology/approach: This study recruited 118 workers from three healthcare facilities through an online and paper survey. Findings: Work-related musculoskeletal injury was experienced by 46 per cent of the workers, with low back injuries being most prevalent. There were significant differences in perception of policies and practices for injury prevention among occupational groups, and between workers who have had previous workplace injury experience and those without past injury. Research limitations/implications: Selection bias is possible because of voluntary participation. A larger sample could give stronger statistical power. Practical implications: The perception of workplace policies can vary depending on workers' occupational and injury status. Organisational managers need to pay attention to the diversity among workers when designing and implementing injury prevention and return to work policies. Social implications: Risks for workplace injuries are related to multiple factors, including workplace policies and practices on health and safety. Workers' understanding and response to the policies, programmes, and practices can determine injury outcomes. Originality/value: No previous study has reported on workers' perceptions of workplace policies and practices for injury prevention and return in Manitoba healthcare sector.